2008
DOI: 10.1100/tsw.2008.86
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acupuncture for Health Conditions in Children: A Review

Abstract: Acupuncture has been used to treat a variety of childhood problems; however, the efficacy and safety of pediatric acupuncture remains unclear. This article reviews the existing empirical literature relating to the use of acupuncture for medical conditions in children. A systematic search of the literature revealed that acupuncture has been used to treat five main conditions in children, including pain, nocturnal enuresis, postoperative nausea/vomiting, laryngospasm/stridor, and neurological disorders. Despite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 36 publications
(38 reference statements)
1
20
0
Order By: Relevance
“…42 In support of this, a new outcomes study suggests positive effects in children nonresponsive to usual care. 41 The current authors agree with the earlier overviews by Libonate et al 7 and by Yang et al, 8 which concluded that results are promising and warrant additional research.…”
Section: Nocturnal Enuresissupporting
confidence: 91%
See 3 more Smart Citations
“…42 In support of this, a new outcomes study suggests positive effects in children nonresponsive to usual care. 41 The current authors agree with the earlier overviews by Libonate et al 7 and by Yang et al, 8 which concluded that results are promising and warrant additional research.…”
Section: Nocturnal Enuresissupporting
confidence: 91%
“…Articles were hand-screened and publications that met inclusion criteria for this review were synthesized into a narrative review and synopsis. Articles that were included within the three prior overviews of the pediatric acupuncture literature 5,7,8 are not summarized in this article.…”
Section: Methodsmentioning
confidence: 97%
See 2 more Smart Citations
“…24,29,87,92,93 The majority of the reviewed papers indicate that acupuncture and acupressure may be effective in reducing PONV and POP. This is also in line with the Society for Ambulatory Anesthesia guidelines for the management of PONV.…”
mentioning
confidence: 99%